If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4u + -12 = -6(u + 7) Reorder the terms: -12 + 4u = -6(u + 7) Reorder the terms: -12 + 4u = -6(7 + u) -12 + 4u = (7 * -6 + u * -6) -12 + 4u = (-42 + -6u) Solving -12 + 4u = -42 + -6u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '6u' to each side of the equation. -12 + 4u + 6u = -42 + -6u + 6u Combine like terms: 4u + 6u = 10u -12 + 10u = -42 + -6u + 6u Combine like terms: -6u + 6u = 0 -12 + 10u = -42 + 0 -12 + 10u = -42 Add '12' to each side of the equation. -12 + 12 + 10u = -42 + 12 Combine like terms: -12 + 12 = 0 0 + 10u = -42 + 12 10u = -42 + 12 Combine like terms: -42 + 12 = -30 10u = -30 Divide each side by '10'. u = -3 Simplifying u = -3
| -8/9y=7 | | 5(x+15)=5x+75 | | 4R-4y-8= | | n-17.2=-2.3 | | 4x^2+9+12x=18 | | 12st/4t | | 9x-6y=12 | | -103=2x+6x-7 | | 2(x+5)=2(x+15) | | m-22/6-7m-21/7=1 | | 10y+2y-12=3(4-6y) | | A-4/512 | | 2x-5=10x-5 | | n/3=4n= | | 2(14+8a)=9a | | 25x-10x-6=0 | | 3(x+1)=6y+11 | | 3(3b-5)= | | .75x-2.75=.3x+.83 | | [4x-4]=12 | | 10-66p=52 | | 2(u+3v)=w-50 | | 2+5-6+x=10 | | (a/3)=((a-3)/2) | | 9x==2/3 | | 2x+4y-4z=-12 | | (a/3)/((a-3)/2) | | 20=a(a-8) | | 2x+6=8+5x | | 450/0.09 | | [7x-7]=21 | | [(y*2/3)^4]/[(y^-1)^1/6] |